Dielectric tensor for a plasma with a loss-cone kappa-Maxwellian velocity distribution - Singhal R.P.; Tripathi A.K. (My University, 2025)
Components of the dielectric tensor are obtained for a kappa-Maxwellian velocity distribution with loss-cone feature for a hot, infinite, homogeneous plasma immersed in a uniform magnetic field. Expansions valid for small propagation angle (angle between the wave vector and the ambient magnetic field) are given for the elements of the dielectric tensor. © 2006 American Institute of Physics.